What became of Paul Dirac's classmate?. Issue 3 (2nd September 2018) - Crilly, Tony
Abstract : We examine Paul Dirac's early life in Bristol and the link with his classmate Herbert Charles Wiltshire. We outline Wiltshire's subsequent career using archives and the few letters which survive between Dirac and Wiltshire.